SISTEM PEMESANAN KAMAR HOTEL BERBASIS WEB - Jeremy Sagala; Bias Yulisa Geni (Yayasan Pendidikan Cahaya Budaya Indonesia, 2026)
The hospitality industry is experiencing rapid growth driven by the adoption of information technology, particularly in hotel reservation systems. Hotel Pinangsia, which still relies on a manual reservation system, faces several issues related to operational inefficiency, record-keeping errors, and limited real-time availability information. This study aims to design and develop a web-based reservation system to address these problems. The software development method used is Agile with the Scrum approach, which includes requirements gathering, sprint planning, iterative development, system testing, and implementation. The main programming language used is JavaScript with the Next.js framework for both frontend and backend development. Database management is handled using the Prisma ORM, connected to a PostgreSQL database hosted on the cloud via Aiven services. The system is also integrated with Xendit as the payment gateway provider, enabling online transaction processing. Key features of the system include